2015
DOI: 10.3389/fpsyg.2015.01304
|View full text |Cite
|
Sign up to set email alerts
|

Boundaryless career and career success: the impact of emotional and social competencies

Abstract: Even though, over the last two decades, the boundaryless career concept has stimulated a wide theoretical debate, scholars have recently claimed that research on the competencies that are necessary for managing a cross-boundary career is still incomplete. Similarly, the literature on emotional and social competencies has demonstrated how they predict work performance across industries and jobs but has neglected their influence in explaining the individual's mobility across boundaries and their impact on career… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(20 citation statements)
references
References 125 publications
2
18
0
Order By: Relevance
“…Studies taking this approach found that among executives, the variety of roles and responsibilities (e.g., contributor, manager, lead strategist) in past working experiences positively predicted their strategic thinking competency (Dragoni, Oh, Vankatwyk, & Tesluk, 2011), and the composite indicator of career boundarylessness (e.g., the number of positions, firms, industries in their career histories) positively predicted executives' pay (Custodio, Ferreira, & Matos, 2013). Similarly, it was found that overall career boundarylessness predicted more promotions among a sample of Italian MBA alumni (Gerli, Bonesso, & Pizzi, 2015), higher levels of knowing-why and knowing-how competencies, career autonomy, career satisfaction and lower levels of career insecurity among American MBA samples (Colakoglu, 2011;Stumpf, 2014), as well as higher levels of career adaptability and competencies among Chinese HR professionals (Guan, Yang, Zhou, Tian, & Eves, 2016).…”
Section: Overall Career Boundarylessness and Career Successmentioning
confidence: 87%
See 1 more Smart Citation
“…Studies taking this approach found that among executives, the variety of roles and responsibilities (e.g., contributor, manager, lead strategist) in past working experiences positively predicted their strategic thinking competency (Dragoni, Oh, Vankatwyk, & Tesluk, 2011), and the composite indicator of career boundarylessness (e.g., the number of positions, firms, industries in their career histories) positively predicted executives' pay (Custodio, Ferreira, & Matos, 2013). Similarly, it was found that overall career boundarylessness predicted more promotions among a sample of Italian MBA alumni (Gerli, Bonesso, & Pizzi, 2015), higher levels of knowing-why and knowing-how competencies, career autonomy, career satisfaction and lower levels of career insecurity among American MBA samples (Colakoglu, 2011;Stumpf, 2014), as well as higher levels of career adaptability and competencies among Chinese HR professionals (Guan, Yang, Zhou, Tian, & Eves, 2016).…”
Section: Overall Career Boundarylessness and Career Successmentioning
confidence: 87%
“…Although it was found that the overall career boundarylessness and the number of employer changes positively predicted managers' status and promotions (Cheramie et al, 2007;Gerli et al, 2015), researchers among CEOs and top managers suggested that their promotions were more based on steady progression within the company but not external mobility between firms and industries (Blair-Loy, 1999;Koch et al, 2017). It was also found that in the UK IT industry, job candidates' past inter-organizational mobility and industrial mobility had negative effects on the probability of being shortlisted for permanent positions (King et al, 2005).…”
Section: Career Boundarylessness and Status Promotion And Reemploymementioning
confidence: 99%
“…In our study, the level of career satisfaction was the highest, which Hierarchical regression showed that the more satisfied the nurses were with their income, the higher the career success rating. Income is an objective evaluation index of career success (Gerli, Bonesso, & Pizzi, 2015). Many researchers have shown that higher incomes for nurses are closely related with higher job satisfaction (Atefi, Lim-Abdullah, Wong, & Mazlom, 2015;Sansoni et al, 2016).…”
Section: Job-related Characteristics and Career Successmentioning
confidence: 99%
“…This individual competence would make someone be more noticeable than the others. Competence is also needed so an individual can change his / her job (Gerli, Bonesso, & Pizzi, 2015). Poor individual competence can mean low expectation to gain opportunities for a new job that will make it harder for an individual to tend to change organizations easily.…”
Section: Resultsmentioning
confidence: 99%